2020
DOI: 10.3390/su12062543
|View full text |Cite
|
Sign up to set email alerts
|

A Spatiotemporal Analysis of the Effects of Urbanization’s Socio-Economic Factors on Landscape Patterns Considering Operational Scales

Abstract: Landscape patterns are significantly affected during the urbanization process. Identifying the spatiotemporal impacts of urbanization’s socio-economic factors on landscape patterns is very important and can provide scientific evidence to support urban ecological management and guide managers to establish appropriate sustainability policies. This article applies multiscale geographically weighted regression (MGWR) to reveal the relationships between landscape patterns and the socio-economic factors of urbanizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…The significant impact range was small and concentrated in the southwestern mountainous hilly area; the differences in the impact of GPUA were not significant between the different regions. Previous studies have shown that human activities have a complex role in landscape fragmentation [51]. These findings suggest that in underdeveloped areas, human economic activities are one of the causes of landscape fragmentation.…”
Section: ) Coefficient Space Pattern Analysismentioning
confidence: 86%
See 2 more Smart Citations
“…The significant impact range was small and concentrated in the southwestern mountainous hilly area; the differences in the impact of GPUA were not significant between the different regions. Previous studies have shown that human activities have a complex role in landscape fragmentation [51]. These findings suggest that in underdeveloped areas, human economic activities are one of the causes of landscape fragmentation.…”
Section: ) Coefficient Space Pattern Analysismentioning
confidence: 86%
“…Intercept distances may help to identify other spatial determinants. Previous evidence indicates that factors such as distance from large cities and urbanization rates may influence the degree of landscape fragmentation [15,51]. Thus, it will be necessary to consider these determinants in future multi-scale analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, demographic structures (e.g., by age) have different impacts on urban growth, since population aging strengthens concentration tendencies, and population growth acts as a dispersion force [61][62][63][64]. This assumption allows a refined assessment of agglomeration forces under multiple demographic scenarios, considering also other disciplinary dimensions and operational scales of analysis and planning, e.g., landscape [65]. Further approaches have been proposed to evaluate the contribution of demographic behaviors to natural population growth and, thus, metropolitan expansion [38].…”
Section: Discussionmentioning
confidence: 99%
“…Human activities strongly affect the natural conditions, hydrological conditions, meteorological characteristics, surface structure, flora, and fauna of the urban landscape [30][31][32][33]. The characteristics of the urban landscape reflect the level of socio-economic development, as well as historical and cultural characteristics [34,35]. In urban landscapes, the structure of the main ingredients is artificial and modified as a basic pattern of the landscape.…”
Section: Introductionmentioning
confidence: 99%